2010
DOI: 10.1007/s10803-010-1108-6
|View full text |Cite
|
Sign up to set email alerts
|

Picture Me Playing: Increasing Pretend Play Dialogue of Children with Autism Spectrum Disorders

Abstract: This study examined the effectiveness of the Picture Me Playing intervention for increasing the play dialogue of preschool children with ASD during pretend play opportunities with typical peers. Picture Me Playing is a pictorially enhanced, script based intervention targeting character role play through a narrative vignette. A single-treatment counterbalanced design was utilized to contrast the performance of intervention and comparison groups, followed by within-subject analysis. Results indicated significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 40 publications
0
9
0
6
Order By: Relevance
“…Youth with ASD may experience difficulty imitating others' gestures and faces (Lainé, Rauzy, Tardif, & Gepner, 2011), inferring mental states of others (Baron-Cohen, Jolliffe, Mortimore, & Robertson, 1997), and orienting focus to a shared object (Pruett et al, 2011). They may play less effectively than typically developing peers (Anderson, Moore, Godfrey, & Fletcher-Flinn, 2004) because they often find initiating and responding to social bids challenging (Murdock & Hobbs, 2011). They are generally less able to participate meaningfully in complex imaginative games, an inability that may limit the attention they receive from peers (Jordan, 2003).…”
mentioning
confidence: 99%
“…Youth with ASD may experience difficulty imitating others' gestures and faces (Lainé, Rauzy, Tardif, & Gepner, 2011), inferring mental states of others (Baron-Cohen, Jolliffe, Mortimore, & Robertson, 1997), and orienting focus to a shared object (Pruett et al, 2011). They may play less effectively than typically developing peers (Anderson, Moore, Godfrey, & Fletcher-Flinn, 2004) because they often find initiating and responding to social bids challenging (Murdock & Hobbs, 2011). They are generally less able to participate meaningfully in complex imaginative games, an inability that may limit the attention they receive from peers (Jordan, 2003).…”
mentioning
confidence: 99%
“…There are various interventions given to children with autism to regain their ability to pretend play. In a study conducted by Murdock and Hobbs (2011), used the Picture Me Playing intervention to enhance the pretend play skills in preschool autistic and typically developed children. According to Smily et al, (2015) stated the Imitation learning for ten weeks of intervention in children with autism and showed improvement in imitation play skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, behavioural treatment could represent the effective intervention strategy for autism [2123]. A plethora of behavioural strategies and social skill trainings have been used [2426]. However, it has been demonstrated that no definitive behavioural intervention completely improves all symptoms for all ASD patients [27, 28].…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%